Model Oriented Dynamic Resource Allocation Basedon Mixed-Game Theory Within Virtual Network - Yu Wang; Minghai Xu; Huan Chi; Xijuan Su (Dianxin kexue)
The traditiona1 internet architecture mode1 is difficu1t to meet the consumers' end1ess emerging app1ications.As the technica1 means that wi11 so1ve the current internet rigid prob1em network virtua1ization has been wide1y noted by the next-generation network research in domestic and foreign fie1d in recent years.Nove1 resource a11ocation a1gorithm that can meet the resource requirements of the virtua1 network users and maximize the use of physica1 network resources under the heterogeneous physica1 environment is the most urgent prob1em for network virtua1ization.According to the thought of game theory, the mixture of game competition mode1 was proposed using cooperative game and non-cooperative game.Besides, virtua1 network was divided into different service types according to the service types.After that, the method of dynamic resource a11ocation within virtua1 networks was proposed.The simu1ation resu1ts show that, the proposed oriented dynamic resource a11ocation within virtua1 networks based on the mixed-game theory scheme can make fu11 use of physica1 resources provided by the InP.At the same time, this scheme can prevent 1ink congestion effective1y and increase the customer satisfaction compared with the traditiona1 resources a11ocation scheme.